PERFORMANCE TESTING OF ACADEMIC WEBSITE USING LOAD TESTING METHOD SUPPORTED BY APACHE JMETERTM AT XYZ UNIVERSITY - Raweyai, Soni Sampari; Widiasari, Indrastanti Ratna (Jurnal Teknik Informatika (Jutif), 2024)
This study aims to evaluate the performance quality of the academic website of University XYZ through load testing using the Load Testing Method supported by Apache JMeterTM. The main issue addressed is how the website's performance can be measured and assessed in the context of normal, peak, and stress usage. The research methodology involves a qualitative approach to understand the meaning, interpretation, and context of the phenomenon, coupled with a quantitative approach to measure, analyze, and organize data in numerical or statistical forms. The research findings indicate that in the basic testing scenario, the website successfully met the test criteria with an average response time of approximately 0.855 seconds for GET requests, below the established maximum limit. POST requests required an average time of around 0.273 seconds with no response failures. In the peak testing scenario simulating high traffic conditions, the website remained optimal with average response times for both GET and POST requests below the 3-second limit, without response failures. Stress testing scenarios demonstrated the efficient operation of the website, even though the average response time for GET requests increased to approximately 2.564 seconds.The test results affirm that the University XYZ website functions well under various service usage conditions, including heavy loads. The overall average response time for GET requests across all scenarios is approximately 1.558 seconds, while POST requests have an average response time of around 0.355 seconds. Special attention is given to the impact of the number of threads or users and the number of students on the website's performance.